Pengembangan Bahan Ajar Berbasis Permainan Tradisional untuk Meningkatkan Perkembangan Anak Usia Dini - Winda, Elvis (UIN Fatmawati Sukarno Bengkulu, 2025)
Research aims to develop valid traditional game-based teaching materials to improve the development of children's religious and social emotional values at Nabilah Kindergarten, Bengkulu City. Type of research is Research and Development (R&D) using the ADDIE development model, namely analysis, design, development, implementation, evaluation. Subjects were 14 children. Instruments used validation sheets (material experts, language experts, practitioner experts), teacher response questionnaires, pretest and posttest. Results were validated by validators from 3 expert teams, namely material experts with a percentage of 95%, language experts of 95%, and practitioner experts of 97.5% in the very valid category. Assessment sheet on the practicality of teachers' responses to teaching materials that have been developed have an average score of 88.8% in the very practical category. Pretest results obtained were 2.0 with poor assessment criteria and the posttest results were 4.1 with good criteria, this shows that traditional game-based teaching materials are effective for children